Gynaecological emergencies. Issue 2 (February 2019) - Gray, Thomas; McQueen, Victoria; Farkas, Andrew
Gynaecological problems in primary care are common. Some gynaecological conditions present as emergencies, requiring rapid referral to secondary care for review and treatment. GPs are likely to see such patients more often in out-of-hours sessions. This article will consider common gynaecological emergencies including pelvic inflammatory disease, bleeding and pain in early pregnancy, vulval abscess, Bartholin's cyst abscess and ovarian cyst accidents. The article aims to guide assessment of patients in primary care including information on aetiology, risk factors, clinical features, initial investigations, management and referral.